"Nadodrze" czasopismem integrującym Ziemię Lubuską = "Nadodrze" as a magazine contributing to social integration in the Lubusz Region - Domke, Radosław (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article addresses the issue of the relationship between processes of social integration taking place in the Lubusz Region, and articles published in the journal "Nadodrze", in the years 1957-1990. It raises issues relating to both political and economic integration, as well as social and cultural integration. The text also attempts to determine what proportions of the contents of "Nadodrze" related specifically to the northern and southern parts of the region. Finally, the article stresses the real importance of cultural topics discussed in the pages of the newspaper, in the context of the integration of the entire Środkowe Nadodrze region (the Middle Oder Region).
Keywords: Nadodrze (czasopismo); nadodrze; czasopisma; Ziemia Lubuska; integracja społeczna; magazines; Lubusz Land; social integration